Divers risk accelerated fatigue and core temperature rise during fully-immersed exercise in warmer water temperature extremes. Issue 2 (3rd April 2019) - Looney, David P.; Long, Edwin T.; Potter, Adam W.; Xu, Xiaojiang; Friedl, Karl E.; Hoyt, Reed W.; Chalmers, Christopher R.; Buller, Mark J.; Florian, John P.
ABSTRACT: Physiological responses to work in cold water have been well studied but little is known about the effects of exercise in warm water; an overlooked but critical issue for certain military, scientific, recreational, and professional diving operations. This investigation examined core temperature responses to fatiguing, fully-immersed exercise in extremely warm waters. Twenty-one male U.S. Navy divers (body mass, 87.3 ± 12.3 kg) were monitored during rest and fatiguing exercise while fully-immersed in four different water temperatures (Tw): 34.4, 35.8, 37.2, and 38.6°C (Tw34.4, Tw35.8, Tw37.2, and Tw38.6 respectively). Participants exercised on an underwater cycle ergometer until volitional fatigue or core temperature limits were reached. Core body temperature and heart rate were monitored continuously. Trial performance time decreased significantly as water temperature increased (Tw34.4, 174 ± 12 min; Tw35.8, 115 ± 13 min; Tw37.2, 50 ± 13 min; Tw38.6, 34 ± 14 min). Peak core body temperature during work was significantly lower in Tw34.4 water (38.31 ± 0.49°C) than in warmer temperatures (Tw35.8, 38.60 ± 0.55°C; Tw37.2, 38.82 ± 0.76°C; Tw38.6, 38.97 ± 0.65°C). Core body temperature rate of change increased significantly with warmer water temperature (Tw34.4, 0.39 ± 0.28°C·h −1 ; Tw35.8, 0.80 ± 0.19°C·h −1 ; Tw37.2, 2.02 ± 0.31°C·h −1 ; Tw38.6, 3.54 ± 0.41°C·h −1 ). Physically active divers risk severe hyperthermia in warmer waters. Increases in water temperature drastically increase the rate of core body temperature rise during work in warm water. New predictive models for core temperature based on workload and duration of warm water exposure are needed to ensure warm water diving safety.